Creatine and cellular senescence: from molecular pathways to populational health - Sergej M. Ostojic; Viktória Prémusz; Pongrác Ács (Experimental Gerontology)
Emerging evidence suggests that creatine, a naturally occurring amino acid derivative and conditionally essential nutrient, may modulate cellular senescence through mechanisms such as enhancing cellular energy homeostasis, mitigating oxidative stress, and influencing key signaling pathways implicated in aging processes. This review critically evaluates the current body of research, highlights existing gaps in the mechanistic understanding, and emphasizes the importance of targeted studies to further delineate creatine's role in cellular senescence and age-associated dysfunctions. By integrating perspectives from molecular biology, gerontology, and applied physiology, this paper aims to advance the understanding of creatine-based strategies as potential interventions for promoting healthy aging and preventing senescence-associated conditions.